Hilda Sabato: itinerarios, horizontes y problemas para la historia política - Hilda Sabato; Margarita Garrido; Franz Hensel; Francisco A. Ortega (Historia Crítica)
Hilda Sabato is a referent of Hispano-American historiography. As a result of the launching of the first volume of the editorial project Historias de lo político en Colombia: imaginando repúblicas en tiempos de independencia, 1780-1852 (Bogotá: Universidad Nacional de Colombia; Universidad del Rosario, 2024), we took advantage of Hilda Sabato's presence in Bogotá to talk with her about the familial, political and intellectual context of her formative years, her experience amid the dictatorships in the Southern Cone, her return to Argentina in the late 1970s and the process of democratic and institutional reconstruction, particularly in the university sphere. We also talked about her concerns and theoretical approaches in the political sphere, as well as her view of the configuration of the republic after the monarchical fracture and the construction of political communities throughout the nineteenth century. In short, the interview addresses the problems and questions that Sabato has sought to resolve through her extensive bibliography.